2013
DOI: 10.4236/jbbs.2013.38063
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Hypobaric Hypoxia and Reoxygenation Induces Transient Anxiety-Like Behavior in Rat

Abstract: Chronic exposure to hypobaric hypoxia (HH) causes memory impairment and prolonged state of mental confusion. However, effect of high altitude exposure on mood state and its underlying mechanisms have been poorly studied. Present study was undertaken to investigate the mood state alteration following chronic exposure to HH. Male Sprague Dawley rats were divided into five groups and exposed to hypoxia for 3, 7, 14 and 21 days in an animal decompression chamber at an altitude of 25,000ft. Anxiety-and depression-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…For comparison, the effect of e2-I injection under normoxic conditions is negligible. Consistent with previous reports (Baitharu et al, 2013), hypoxia decrease the rearing counts of mice ( Fig EV6A). And the e2-I injection further decreased the rearing counts of mice to half, compared with scrambled peptide injection ( Fig EV6A).…”
Section: Mammalian-unique Eif4e2 Protects Tissues Against Hypoxiasupporting
confidence: 93%
“…For comparison, the effect of e2-I injection under normoxic conditions is negligible. Consistent with previous reports (Baitharu et al, 2013), hypoxia decrease the rearing counts of mice ( Fig EV6A). And the e2-I injection further decreased the rearing counts of mice to half, compared with scrambled peptide injection ( Fig EV6A).…”
Section: Mammalian-unique Eif4e2 Protects Tissues Against Hypoxiasupporting
confidence: 93%
“…Prolonged exposure to hypobaric hypoxia is known to causes glutamate excitotoxicity, hippocampal neurodegeneration and cognitive dysfunction [ 22 , 27 ]. Recent study by Baitharu et al (2013) showed that hypobaric hypoxia induced alteration in mood state is transient in nature which get normalised with prolonged exposure [ 28 , 32 ].Further, prolonged hypoxic exposure causes decrease in food and water intake and consequent loss of body weight [ 33 , 34 ]. Exposure to restraint or immobilisation stress has been reported to induce psychosocial disorders in animal [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of behavioural impairment along with structural as well as morphological alterations in various brain regions following exposure to chronic restraint/crowding stress is well documented. Though effect of hypobaric hypoxia on mood state alteration have been shown to be transient in nature [ 28 ], Combination of hypoxia and crowding stress could exert robust influence on mood state and precipitate anxiety and depression like behaviour following prolonged exposure. Keeping in mind the elevated nitric oxide level in the brain following hypoxic exposure, we attempted to explore the relationship between the nitric oxide and microglial activation following CHC stress exposure and further evaluated the therapeutic efficacy of L-NAME in ameliorating CHC induced depressive mood state.…”
Section: Introductionmentioning
confidence: 99%
“…The rats was placed in one corner of the open filed and its activity during the subsequent 5 min was assessed. Locomotion (central zone crossing) and time spent in central and peripheral zone were observed [ 24 ].…”
Section: Methodsmentioning
confidence: 99%